2015
DOI: 10.1136/postgradmedj-2014-132967
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of demographic factors affecting performance in a paediatric membership multiple-choice examination

Abstract: MRCPCH part 1B outcome was related to place of primary medical qualification, with a significantly lower pass rate for international medical graduates compared with UK graduates, as well as significant variation in examination outcome between graduates from different UK medical schools. These data may be used to guide new initiatives to improve support and education for these trainees and to inform development of undergraduate curricula and help trainees prepare more successfully for postgraduate examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We have been unable to find exactly comparable data from medical licensing examinations in other countries. A UK retrospective analysis observed that international graduates aged more than 37 years actually performed better in a postgraduate paediatric examination 17. However, a US analysis noted a negative correlation between age when first certified by the American Board of Internal Medicine and the American Board of Surgery and subsequent success in maintenance of certification examinations 18…”
Section: Commentarymentioning
confidence: 99%
“…We have been unable to find exactly comparable data from medical licensing examinations in other countries. A UK retrospective analysis observed that international graduates aged more than 37 years actually performed better in a postgraduate paediatric examination 17. However, a US analysis noted a negative correlation between age when first certified by the American Board of Internal Medicine and the American Board of Surgery and subsequent success in maintenance of certification examinations 18…”
Section: Commentarymentioning
confidence: 99%
“…We included 23 retrospective observational studies, one prospective cohort study 28 , and one case-control study. 29 Seven studies were from Canada 12,14,15,27,[30][31][32] , eight from the USA 25,26,29,[33][34][35][36][37] , seven from the United Kingdom 1,[38][39][40][41][42][43] , and one each from Australia 7 , Sweden 28 and Finland 44 . Four were single-institution studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The remaining two studies 39,44 showed a statistically nonsigni cant association between age and success in certi cation exams. Six studies 15,30,39,41,42,44 explored the associations between female sex and success in certi cation exams, with ve studies 15,30,39,41,44 indicating that female candidates were more likely to succeed in various certi cation exams.…”
Section: Success In Qualifying Examsmentioning
confidence: 99%
“…Research has also demonstrated that female doctors perform better academically, 6 particularly in clinical 7-10 rather than written assessments. 7,11,12…”
Section: Introductionmentioning
confidence: 99%